Dual Career Development Perspective: Factors Affecting Quality of Post-sport Career Transition of Employed Olympic Athletes - Robnik, Petra; Kolar, Edvard; Štrumbelj, Boro; Ferjan, Marko (Frontiers in Psychology, 2022)
Although Olympic athletes are celebrated for their sports achievements, they often face serious difficulties in their post-sport career employment. Factors of development that are affecting the quality of post-sport career transition of Olympic athletes are important to acknowledge in the dual career (DC) development perspective. Due to the side lining of academic activities, athletes are often not well prepared for the labor market. If they do not gain sufficient financial background in their careers, it can lead to a lack of proper economic inclusion of athletes in their post-sport career employment and further impact their lives. Career transitions of athletes have been the subject of research in different aspects of DC support (e.g., athletic, psychological, psychosocial, academic/vocational, financial), but most research is linked to the student-athlete DC perspective. Therefore, the aim of our research was to examine the impact of factors directly contributing to the quality of the post-sport career transition in Slovenian elite and Olympic athletes and the social class position and employment of these athletes after the termination of their sports career. From DC support practice, we learned that although athletes often have a proper level of education, their post-sport career transitions were not successful. To fill this gap, 168 elite athletes (Mage = 33.34, SD = 13.1) from Slovenia were asked to complete online questionnaires. The results showed a significant contribution of education and DC support-related finances (e.g., employment of athletes in public administration) to the quality of post-sport career transition. Regarding developing a national DC model and based on empirical research, this study identifies the social class position and employment status of former elite athletes from Slovenia. It also identifies opportunities for further research on the quality of the post-sport career transitions and perspectives on DC support. Understanding how different factors contribute to the integrated development of individual athletes to reach their potential in sports, education, and their post-sport career employment is important for theorists, DC practitioners, and stakeholders working with DC athletes. To develop a sufficient mechanism, DC support providers should consider supporting education along with the financial support of athletes during their sports careers and recognizing study-training ecosystems, based on good practices to successfully transition to their post-sport careers. These findings can also be useful for athletes and their athletic triangle support network (e.g., coaches and parents) as a support in the decision-making.